2014
DOI: 10.1186/1476-4598-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Bosutinib inhibits migration and invasion via ack1 in kras mutant non-small cell lung cancer

Abstract: The advent of effective targeted therapeutics has led to increasing emphasis on precise biomarkers for accurate patient stratification. Here, we describe the role of ACK1, a non-receptor tyrosine kinase in abrogating migration and invasion in KRAS mutant lung adenocarcinoma. Bosutinib, which inhibits ACK1 at 2.7 nM IC50, was found to inhibit cell migration and invasion but not viability in a panel of non-small cell lung cancer (NSCLC) cell lines. Knockdown of ACK1 abrogated bosutinib-induced inhibition of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 31 publications
2
49
1
Order By: Relevance
“…It was reported in many studies that miR-940 was highly expressed in normal tissues compared with tumors, and miR-940 was shown to inhibit the migratory and invasive potential of cancer cells by suppressing CXCR2 [59], MIEN1 [58], MyD88 [57], Nestin [56], and ZNF24 [54]. Moreover, the Estrogen-Related Receptor Gamma (ESRRG) was targeted by miR-940, and suppression of ESRRG inhibited hepatocellular carcinoma cell lines growth and induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in many studies that miR-940 was highly expressed in normal tissues compared with tumors, and miR-940 was shown to inhibit the migratory and invasive potential of cancer cells by suppressing CXCR2 [59], MIEN1 [58], MyD88 [57], Nestin [56], and ZNF24 [54]. Moreover, the Estrogen-Related Receptor Gamma (ESRRG) was targeted by miR-940, and suppression of ESRRG inhibited hepatocellular carcinoma cell lines growth and induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among all the glycolytic enzymes, LDH is of great importance to maintain high glycolysis rate. And LDHA is reported to be up-regulated in many cancers [16, 17, 1921, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…ACK1, an intracellular tyrosine kinase, is considered to be implicated in regulating multiple aspects of tumor progression (13,16). Several studies have indicated that ACK1 overexpression is commonly observed in human cancers including lung and prostate cancer (27,33). Furthermore, it has been demonstrated that ACK1 can promote tumor growth via regulating pro-survival molecules such as AKT and AR in various cancers (26,31,33).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have implicated ACK1 amplification and high-expression in carcinogenesis of multiple tissue types such as lung, breast and prostate (27)(28)(29). Overexpression level of ACK1 correlates with tumor invasion and migration in renal and pancreatic cancers (30,31).…”
Section: Introductionmentioning
confidence: 99%